"ETUDE DU COMPORTEMENT D’UN BARRAGES EN BETON : Cas du barrage de Fontaine de gazelle (Wilaya de Biskra)" - يمينة, جنايحي; فاطمة, زوبير (University of El-Oued, 2020)
"Monitoring of the actual behavior of the dam not only during construction and during filling, but is necessary during operation of the dam boundaries to ensure the proper behavior of these structures This study was conducted on the data of the land dam, fontaine de gazelle, located in the municipality of Lataya, north of Biskra, recently. The study aims to evaluate the behavior of the dam on the basis of interpretation. Monitoring procedures and recommendations to improve the general safety of the dam. In the analysis we rely mainly on treating the auscultation values available for judgment, the general behavior of the dam, the phenomena related to the development of interstitial stresses, and the measurement of pressure at the level of the central core of the dam. As well as climatic phenomena and the tassometry and piezometric curves. The results showed that the case of the deer source dam is exposed to many leaks and to reduce them, many techniques must be introduced to limit the leakage process and in order not to aggravate and cause a disaster in the dam that we can never control. " "مراقبة السلوك الفعلي لسد ليس فقط اثناء البناء وأثناء التعبئة ولكن من الضروري خلال تشغيل حدود السد لضمان حسن سلوك هده الهياكل. اجريت هده الدراسة على البيانات الخاصة بسد الارضي منبع الغزلان الواقع في بلدية لوطاية شمال ولاية بسكرة في اونة الاخيرة تهدف الدراسة الى تقييم سلوك السد على اساس تفسير تدابير المراقبة وتقديم توصيات من اجل تحسين المستوى العام لسلامة السد .يعتبر تسرب مياه السد ومشكلة التوحل من بين مشاكله نعتمد في تحليل بشكل اساسي على معالجة قيم التسمع المتاحة للحكم وعلى سلوك عام لسد والظواهر المتعلقة بتطور الضغوط الخلالية وقياس الضغط على مستوى اللب المركزي للسد وكدا الظواهر المناخية ومنحنيات مقاييس الضغط اظهرت النتائج ان حالة سد منبع الغزلان يتعرض للعديد من التسربات وللحد منها يجب تدخل العديد التقنيات للحد من عملية التسرب و لكي لا تتفاقم وتحدث كارثة في السد لا نستطيع التحكم فيها ابدا. "
ovrage hydraulique مذكرة ماستر تخصص
Keywords: comportement réel; السلوك الفعلي لسد